Safety, quality, and microbial community analysis of salt-fermented shrimp (Saeu-jeot) in South Korea - Heeyoung Lee; Hyunjin Cho; Yeongsil Lim; Sunhyun Park; Jeeyeon Lee (Heliyon, 2024)
This study thoroughly explores the quality and safety aspects of saeu-jeot, a popular salt-fermented shrimp in South Korea, with a specific focus on products fermented in underground tunnels. In this study, an extensive analysis of key quality factors (pH, salinity, total nitrogen [TN], and amino nitrogen [AN]), along with detailed investigation into chemical hazards (volatile basic nitrogen [VBN] and biogenic amines [BAs]), and microbiological hazards (total aerobic bacteria [TAB], fecal indicator bacteria, halophilic bacteria, and foodborne pathogens) were performed. The results indicate that the shrimp grade did not dramatically affect the quality and safety of the saeu-jeot. However, given the prevalent small-scale production of saeu-jeot, the study strongly underscores the pressing need for the establishment of a standardized manufacturing process. The absence of grade-dependent variations in quality highlights the critical importance of implementing standardized procedures to ensure the consistent quality and safety of saeu-jeot, particularly in the context of its frequent small-scale production. These findings provide crucial insights for the industry to enhance practices and meet quality and safety standards effectively.